Cathepsins and Parkinson’s disease: insights from Mendelian randomization analyses - Yusufujiang, Aishanjiang; Zeng, Shan; Li, Hongyan (Frontiers in Aging Neuroscience, 2024)
Background: Parkinson's disease (PD), the second most prevalent neurodegenerative condition, has a multifaceted etiology. Cathepsin-cysteine proteases situated within lysosomes participate in a range of physiological and pathological processes, including the degradation of harmful proteins. Prior research has pointed towards a potential link between cathepsins and PD; however, the precise causal relationship between the cathepsin family and PD remains unclear. Methods:This study employed univariate and multivariate Mendelian randomization (MR) analyses to explore the causal relationship between the nine cathepsins and Parkinson's disease (PD) risk. For the primary analysis, genome-wide association study (GWAS) summary statistics for the plasma levels of the nine cathepsins and PD was obtained from the INTERVAL study and the International Parkinson's Disease Genomics Consortium. GWAS for PD replication analysis were obtained from the FinnGen consortium, and a meta-analysis was performed for the primary and replication analyses to evaluate the association between genetically predicted cathepsin plasma levels and PD risk. After identifying significant MR estimates, genetic co-localization analyses were conducted to determine whether shared or distinct causal variants influenced both cathepsins and PD. Results: Elevated cathepsin B levels were associated with a decreased risk of PD in univariate MR analysis (odds ratio [OR]=0.890, 95% confidence interval [CI]: 0.831-0.954, pFDR=0.009). However, there was no indication that PD affected cathepsin B levels (OR=0.965, 95% CI: 0.858-1.087, p=0.852). In addition, after adjusting for the remaining cathepsins, cathepsin B levels independently and significantly contributed to the reduced risk of PD in multivariate MR analysis (OR=0.887, 95% CI: 0.823-0.957, p = 0.002). The results of the replication MR analysis with the FinnGen GWAS for PD (OR=0.921, 95% CI: 0.860-0.987, p = 0.020) and meta-analysis (OR=0.905, 95% CI: 0.862-0.951, p < 0.001) were consistent with those of the primary analysis. Colocalization analysis did not provide any evidence of a shared causal variant between cathepsins and PD (PP.H4.abf = 0.005). Conclusions: This genetic investigation supports the hypothesis that cathepsin B exerts a protective effect against PD. The quantification of cathepsin B levels could potentially serve as a predictive biomarker for susceptibility to PD, providing new insights into the pathomechanisms of the disease and possible interventions.